BEHAVIOR OF BURNING FIRE IN DRY DECIDUOUS DIPTEROCARP FOREST AT HUAI KHA KHAENG WILDLIFE SANCTUARY, UTHAI THANI PROVINCE - Himmapan, Woraphun; Kaitpraneet, San (วารสารวนศาสตร์ไทย, 2022)
Behavior of burning fire in the dry deciduous dipterocarp forest at Huai Kha Khaeng Wildlife Sanctuary was studied in twelve plots, 30 x 30 m2, with completely randomized design and burning in three plots per each month from January to April in 2003 and 2004. Rates of fire spread, flame heights and flame temperature were recorded for every two minutes in eight cardinal directions during burning. Fire line intensity and flame lengths were determined by using Byram’s formula. Comparisons of the result differences among the four months burning, and between the first year and second year were made. The results revealed that the surface fire intensity was not severe. The averages of rate of fire spread, fire line intensity, and flame length from the first year burning were 0.47 m min-1, 66.17 kW m-1 and 0.54 m, respectively, and the averages of those from the second year burning were 0.44 m min-1, 44.33 kW m-1 and 0.45 m, respectively. Most fire descriptors were higher in heavier load and drier fuel months. However, the large amount rain in 2003 and the lower fuel load in 2004 led to low fire intensity.